The Role of STP Marketing Strategy in Enhancing the Marketing Performance of IKM Logam Tembaga, Cepogo Village, Boyolali - Muhammad Saddam Sofyandi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research investigates the role of Segmenting, Targeting, and Positioning (STP) strategies in enhancing the marketing performance of copper handicraft SMEs (IKM Logam Tembaga) in Cepogo Village, Boyolali. A mixed methods approach was used, beginning with a Focus Group Discussion (FGD) involving 15 business owners divided into three groups. The FGD explored the extent to which these entrepreneurs understood and implemented STP principles. Findings revealed that while 53.3% of participants demonstrated explicit awareness of STP, many others intuitively practiced its principles through segmentation, buyer targeting, and product differentiation. This was followed by a quantitative analysis using Structural Equation Modeling (SEM) via SmartPLS, involving 41 IKM respondents. The SEM results show that only Positioning had a statistically significant effect on marketing performance (β = 0.51, p = 0.025), while Segmenting (β = 0.20, p = 0.34) and Targeting (β = 0.07, p = 0.82) did not show significant effects. The measurement model met all validity and reliability thresholds (CR > 0.90, AVE > 0.68), and the model explained 50.1% of the variance in marketing performance. These findings suggest that SMEs with a strong brand narrative, product uniqueness, and storytelling capabilities perform better in the competitive craft market. The research recommends capacity-building programs in STP and digital branding to increase competitiveness among rural SMEs.